2015
DOI: 10.2298/pac1501017s
|View full text |Cite
|
Sign up to set email alerts
|

Processing of porcelain stoneware tile using sugarcane bagasse ash waste

Abstract: Large amounts of waste materials are discarded in the sugarcane industry. This work investigates the reuse of sugarcane bagasse ash waste as an alternative raw material for porcelain stoneware tile bodies, replacing natural quartz by up to 5 wt.%. The tile pieces were fired at 1230 ?C using a fast-firing cycle (< 60min). The technological properties of the fired tile pieces (e.g., linear shrinkage, water absorption, apparent density, and flexural strength) were determined. The sintering pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Fly ash has very fine particles with an average diameter of approximately 10 µm, and it is chemically made of SiO 2 and Al 2 O 3 . Similarly, municipal solid waste ash [21,22], blast furnace slag [23][24][25][26], sewage sludge [27,28], and bagasse ash [29][30][31] have been suggested as raw material for ceramic processing. Furthermore, it has been suggested that materials with superior mechanical strength can be developed using the spark plasma sintering (SPS) method with industrial waste as a ceramic raw material [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fly ash has very fine particles with an average diameter of approximately 10 µm, and it is chemically made of SiO 2 and Al 2 O 3 . Similarly, municipal solid waste ash [21,22], blast furnace slag [23][24][25][26], sewage sludge [27,28], and bagasse ash [29][30][31] have been suggested as raw material for ceramic processing. Furthermore, it has been suggested that materials with superior mechanical strength can be developed using the spark plasma sintering (SPS) method with industrial waste as a ceramic raw material [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the SPS process using RAP as a novel recycling method for concrete waste for application in ceramics processing. According to the ISO 13006 standards, ceramic tiles having strength greater than 35 MPa are better suited for porcelain stoneware tiles [30,46]. We apply the SPS technique for sintering RAP to produce ceramics that have a flexural strength greater than 70 MPa, which is double the value set by the ISO 13006 standards.…”
Section: Introductionmentioning
confidence: 99%
“…The flexural strength gradually decreased with the addition of sugarcane bagasse ash by-products, result which may be related to the porosity of pieces. The incorporation of larger amounts of ash by-products tend to decrease the rate of densification of porcelain stoneware tiles (SCHETTI-NO;HOLANDA, 2015b).…”
Section: Red Ceramic Replacementmentioning
confidence: 99%
“…Schettino and Holanda [58] examined the effect of addition of bagasse ash in the processing of porcelain stoneware. The bagasse ash waste was increased from 0 to 5% through 8 Advances in Materials Science and Engineering 1.25% and 2.5%.…”
Section: Bagasse Ashmentioning
confidence: 99%